Effects of land use, habitat characteristics, and small mammal community composition on Leptospira prevalence in northeast Madagascar. - James P Herrera; Natalie R Wickenkamp; Magali Turpin; Fiona Baudino; Pablo Tortosa; Steven M Goodman; Voahangy Soarimalala; Tamby Nasaina Ranaivoson; Charles L Nunn (Public Library of Science (PLoS), 2020)
Human activities can increase or decrease risks of acquiring a zoonotic disease, notably by affecting the composition and abundance of hosts. This study investigated the links between land use and infectious disease risk in northeast Madagascar, where human subsistence activities and population growth are encroaching on native habitats and the associated biota. We collected new data on pathogenic Leptospira, which are bacteria maintained in small mammal reservoirs. Transmission can occur through close contact, but most frequently through indirect contact with water contaminated by the urine of infected hosts. The probability of infection and prevalence was compared across a gradient of natural moist evergreen forest, nearby forest fragments, flooded rice and other types of agricultural fields, and in homes in a rural village. Using these data, we tested specific hypotheses for how land use alters ecological communities and influences disease transmission. The relative abundance and proportion of exotic species was highest in the anthropogenic habitats, while the relative abundance of native species was highest in the forested habitats. Prevalence of Leptospira was significantly higher in introduced compared to endemic species. Lastly, the probability of infection with Leptospira was highest in introduced small mammal species, and lower in forest fragments compared to other habitat types. Our results highlight how human land use affects the small mammal community composition and in turn disease dynamics. Introduced species likely transmit Leptospira to native species where they co-occur, and may displace the Leptospira species naturally occurring in Madagascar. The frequent spatial overlap of people and introduced species likely also has consequences for public health.